Age and Sex-Related Differences in the Tongue Pressure Generated during Maximum Isometric and Swallowing Tasks by Healthy Chinese Adults - Lin, Wen-Yu (Int J Environ Res Public Health, 2021)
The aims of this prospective observational study were to investigate age, sex, and factors related to the tongue pressure generated. A correlational research design was used. A total of 150 Chinese people who had a normal swallowing condition were enrolled by convenience sampling. Pressure was measured for each participant during maximum isometric press tasks, as well as for saliva and water swallows (5 mL) at the anterior and posterior tongue. The results illustrated that age has an impact on anterior tongue pressure (r = −0.22), posterior tongue pressure (r = −0.26); however, it does not have an impact on the swallowing pressure (SP) of the tongue. Sex differences were noted; males demonstrated a greater strength of the anterior tongue. There was a significant correlation between BMI and the maximum isometric pressure of the anterior tongue (MIP(ant)). The pressures between anterior and posterior tongue were not significantly different in the maximum isometric or swallowing tasks. There were significant differences among the maximum isometric pressure (MIP), saliva swallowing pressure, and water swallowing pressure. The MIP generated was greater than the pressure in the swallowing tasks for the younger groups of both sexes. The study supplement the exploration of age-and-sex related differences and the interaction of sex and age in tongue pressure.